The Right Temporal Lobe and the Enhancement of Voice Recognition in Congenitally Blind Subjects - Terruzzi, Stefano; Papagno, Costanza; Gainotti, Guido (Brain sciences, 2023)
Background: Experimental investigations and clinical observations have shown that not only faces but also voices are predominantly processed by the right hemisphere. Moreover, right brain-damaged patients show more difficulties with voice than with face recognition. Finally, healthy subjects undergoing right temporal anodal stimulation improve their voice but not their face recognition. This asymmetry between face and voice recognition in the right hemisphere could be due to the greater complexity of voice processing. Methods: To further investigate this issue, we tested voice and name recognition in twelve congenitally blind people. Results: The results showed a complete overlap between the components of voice recognition impaired in patients with right temporal damage and those improved in congenitally blind people. Congenitally blind subjects, indeed, scored significantly better than control sighted individuals in voice discrimination and produced fewer false alarms on familiarity judgement of famous voices, corresponding to tests selectively impaired in patients with right temporal lesions. Conclusions: We suggest that task difficulty is a factor that impacts on the degree of its lateralization.